Synthesis and reactions of 3-aminotetrachloroquinazolin-2,4-dione - Hassan, Mamdouh Adly; Younes, Ahmed Mohamed Mosalem; Taha, Mohamed Mobark; Abdel-Monsef, Abou-Bakr Haredy (European Journal of Chemistry, 2011)
N-phenylsulphonyloxytetrachlorophthalimide was obtained by treatment of N-hydroxy tetrachlorophthalimide with benzenesulphonyl chloride. Also, the titled compound 3 was obtained by reaction of compound 2 with hydrazine hydrate via Lossen rearrangement. Compound 3 used as starting material for the synthesis of new pyrimidine and quinazolinedione derivatives containing four chlorine atoms which have pharmacological activity.